Dismissal Disputes and Endogenous Sorting - Pietro Garibaldi; Gerard A. Pfann (Center for Economic Studies and ifo Institute (CESifo), 2015)
Dismissal disputes occur mostly in recessions and often lead to long and costly contract termination procedures. This paper investigates how dispute procedures may affect the job-matching process. First we present a simple accounting framework that corresponds with general dismissal legislation, but is sufficiently flexible to accommodate country-specific legislation. Detailed information from a sample of 2,191 disputes that occurred in the Netherlands between 2006 and 2009 is used to adjust the framework to Dutch institutional specificity. The resulting equilibrium matching model is solved to explain endogenous sorting between lengthy and costly firing procedures. The model also rationalizes the longevity of the dual Dutch model and its political resilience.
Keywords: E24; J08; J38; K31; 330; disputes; firing; legislation; sorting